Sociology of Religious Extremism in The Malay World: An Early Analysis - Yaqut Cholil Qoumas; Rahimin Affandi Abdul Rahim; Mohammad Taufiq Rahman; Jazilus Sakhok (Universitas Islam Negeri Sunan Gunung Djati Bandung, 2023)
The Malay World is known as an area inhabited by gentle and peace-loving people. This happens because this area has a history of interacting with foreign nations and major world religions. However, this image of peace changed when extremist movements appeared in the name of salafi jihad. The main objective of this study is to analyze the Islam-based sociology of extremism based on literature sources. It consists of primary and secondary sources produced by extremists and religious authorities. The data from these two sources are analyzed critically and use a historical perspective to identify the details of this religious extremism's teachings. This study found that the religious extremism detected in the Malay world stems from the understanding of the concepts of takfir and jihad that deviate from the teachings of Islam. These two concepts have been brought to life by the neo-Khawarij (Salafi Jihad) movement that uses ICT, especially modern social media. This causes this religious extremism movement to be welcomed by some community members.